Why highly compliant poles are not energetically beneficial during running: Evidence from an optimization-based biped model. (5th March 2021) - Li, Tong; Li, Qingguo; Liu, Tao
Abstract: Springy poles are a unique load-carrying tool and inspire novel designs of other load-carrying systems. Previous experiments have shown that highly compliant poles with a natural frequency lower than step frequency are more economical than rigid poles during load carriage in walking and this was successfully explained in later modeling studies. However, an energetic benefit was not observed during running with highly compliant poles. We speculate that gait type (running versus walking) may be a factor accounting for the different observations. An optimization-based biped model is adopted to predict the energy cost of load carriage with poles during running, with the parameters from previous experimental studies. The predicted load motion and load-body interaction force agree well with experimental measurements. Compared to running with rigid poles, the highly compliant pole results in reduced peak ground reaction force, longer stance phase duration, and higher energy cost. The changes in running energetics are further found to depend on the natural frequency of the load-pole system relative to the step frequency, but with an opposite trend compared to the changes in walking energetics during pole carriage. Highly compliant poles cost more energy than rigid poles during running, while stiffer poles with a higher natural frequency may offer energetic benefits. This study indicates that the fundamental difference in gait type has a profound influence on the energetic performance of load-carrying devices and this should be taken into consideration in future device designs.